New channel model for wireless body area network with compressed sensing theory. Issue 2 (1st June 2013) - Balouchestani, Mohammadreza; Raahemifar, Kaamran; Krishnan, Sridhar
Abstract : Wireless body area networks (WBANs) consist of small intelligent wireless sensors attached on or implanted in the body to collect vital biomedical data for providing a Continuous Health Monitoring System for diagnostic and therapeutic purposes. To fully exploit the benefits of WBANs the power consumption and sampling rate should be restricted to a minimum. The power usage can be minimised by optimising the features of multipath fading channels (MFCs) such as the number of arrival paths. That is why an improving of MFCs as well as a simple and generic channel model is inevitably required. With this in mind, compressed sensing (CS) theory, as a new sampling procedure, is employed to MFCs. Advance WBANs with the authors new model for MFCs based on CS theory will be able to deliver healthcare not only to patients in hospital and medical centres; but also in their homes and workplaces thus offering cost saving, and improving the quality of life. The authors simulation results illustrate 20% reduction for path loss and 10% for bit‐error rate at gate way (GW). The simulation results also confirm that signal amplitude at GW increases by 25%, which will result in an increase, in the distance, between transmitter and receiver sensors.